(untitled) (Global Journal of Human-Social Science, 2022)
Agribusiness venture has huge function in the economy to foster rural development in the nation The current agribusiness venture in UT of Jammu and Kashmir is mainly in the nature of food processing units They have implications on food security and essential necessities of human beings The present study aims at recognizing qualities shortcomings opportunities and threats for agribusiness ventures with economic and financial perspectives in UT of Jammu and Kashmir to capture market share